Hydrogen Purification From Syngas By Psa Using Microporous Media - Shamsudin, Ili Khairunnisa (2020)
Utilization of renewable energy has become attractive alternative in tackling the problem of global climate change and future energy production. Hydrogen as a soughtafter energy substitute have received increasing support to power a fuel cell system or for safe human consumption. There is an urgent need to purify hydrogen gas from synthetic gas or syngas production of coal gasification in order to recover the spent hydrogen and capture CO2 to address the global issue of climate change more efficiently. One of the main syngas purification technologies, i.e., pressure swing adsorption (PSA) unit coupled with water-gas shift reaction (WGSR) step of gasified feed (H2 and CO2) via precombustion capture could provide cleaner hydrogen recovery for profitable applications. This thesis focused on studying the purification of hydrogen in addition to carbon capture (15 mol%), from a 10 ml/min gas flowrate of H2/CO2 mixture of syngas stream with varied adsorption pressures (1, 2 and 3 bar) in the two-column PSA incorporated with pressure equalization step for less energy penalty and higher hydrogen recovery. Amongst four porous adsorbents prepared, activated and characterized, the reusable and low-cost palm kernel shell activated carbon (PKS-AC) was highlighted to be the best in the hydrogen purification due to its high specific surface area of 697.67 m2/g with relatively high CO2 adsorption capacity of 422.64 cm3 (CO2)/g at STP. The breakthrough time was up to 35 min with adsorption capacity of 7.9733 mg CO2/g. The experimental values fitted a typical type-I Langmuir isotherm of a monolayer adsorption and pseudo one-order model, indicating fully reversible physisorption through film diffusion and intra-particle diffusion as the rate-determining step mechanisms. The porous PKS-AC medium was found effective in achieving CO2/H2 optimum separation at 2 bar, 5 min adsorption time and 5 min blowdown time with 99.99% H2 average purity, 99.99% H2 average recovery and 19.05% CO2 average purity, 7.14% CO2 average recovery.